#Communing affiliation: Social tagging as a resource for aligning around values in social media. (April 2018) - Zappavigna, Michele; Martin, J.R.
Abstract: Social metadata is an important dimension of social media communication, and closely associated with practices such as curating, tagging, and searching content. This article explores how hashtags are used to coordinate and accentuate the values construed in a corpus of Twitter posts (tweets) about depression. In other words, it explores how people use hashtags as a resource to 'convoke' communities of feeling around values realised as ideation-attitude couplings. The aim is to extend work on dialogic affiliation (Knight, 2010a, 2010b, 2013) in order to account for 'ambient' affiliation via social media, where participants do not necessarily interact directly. We employ a discursive system, communing affiliation, to interpret how particular values about depression are positioned as bondable in this ambient environment. The focus is on understanding how people are forging alignments and negotiating meaning through social tagging practices.